IMPLEMENTATION OF YUDHISTIRA SUPPORT CHARACTER VALUE AT MUHAMMADIYAH GIRIKERTO ELEMENTARY SCHOOL - Yeyen Febrilia; Niswi Mukarromah (Indonesian Journal of Elementary Teachers Education, 2022)
This study aims to describe the character values of the Yudhistira wayang character and the implementation of the Yudhistira wayang character values in SD Muhammadiyah Girikerto. This study used a descriptive qualitative method. The object of this research is the character value of the students of SD Muhammadiyah Girikerto. The subjects in this study were principals, teachers and students. The data collection instrument used was in the form of interview and observation guidelines. Data analysis uses the Miles and Huberman model, namely data reduction, display data, and drawing conclusions. The technique of examining data uses triangulation of sources and techniques. The results showed that the students of SD Muhammadiyah Girikerto were able to have characters according to the character values of the Yudhistira puppet character. The character values contained in the wayang Yudhistira are: 1) Religious, 2) Leadership, 3) Honest, and 4) Responsibility. The implementation of the character values of the Yudhistira puppet character is carried out through: 1) Making learning tools, 2) Learning processes such as leading prayers, collecting assignments, and being active in the classroom, and 3) Application of student character values in the school environment. The conclusion from the results of this study is that the character of the wayang Yudhistira contains good character values so that it can be used as character building for students. Based on the results of this study, there are suggestions put forward by the author, namely the cultivation of character values through wayang Yudhistira figures not only limited to learning activities in the classroom but can be implemented in the surrounding environment.